Acute fatigue affects reaction times and reaction consistency in Mixed Martial Arts fighters - Pavelka, R.; Trebický, V.; Trebická Fialová, J.; Zdobinský, A.; Coufalová, K.; Havlicek, J.; Tufano, J. J. (PLOS ONE, 2020)
Mixed Martial Arts (MMA) is a multielement combat sport where fighters need to quickly react to an opponent`s movements under fatigued conditions. Research indicates that fast reaction time is important in many sports, but the effect of fatigue has shown negative, null, or even positive influences on reaction time. However, few studies have been conducted in a controlled setting, especially using MMA figthers, whose matches are frequently resolved in a split-second. Therefore, this study investigated whether acute neuromuscular fatigue affects reaction and movement times, and their consistency in MMA fighters (N = 45). Before and after an upper-body Wingate test, a simple visual reaction time task was completed. Results showed a significant negative effect of fatigue on the reaction times and their consistency, with longer reactions (1.5% change) and lower consistency (14.7% change) after the Wingate test. Further, greater amounts of fatigue during the Wingate test seemed to negatively affect the consistency of post-Wingate movement time. Due to cumulative fatigue and the dynamic nature of MMA, our data indicate that not only the decrements in aerobic and anaerobic power likely affect a fighter`s performance, but their reaction time and motor time may also be compromised during a fight.